Inovasi Pupuk Organik Dan Filter Biogas Berbasis Pengolahan Limbah Bio-Slurry Serta Limbah Baglog di Rumah Qur’an At-Tazkiyyah - Made Sutha Yadnya; Cipta Ramadhani; Teti Zubaidah; Bulkis Kanata; Rosmaliati Rosmaliati (Jurnal Gema Ngabdi, 2026)
Sembalun Bumbung Village, East Lombok, faces the problem of river pollution due to the disposal of livestock manure and garbage (organic waste), which on the other hand has great potential to be processed into fertilizer and biogas as an alternative energy that is economical, environmentally friendly, and sustainable. A boarding school in the At-Tazkiyyah Sembalun Qur'an House which is also a center for community empowerment, in order to meet energy needs while reducing environmental pollution. The methods used include training and assistance to students and the community about the management of waste (organic waste), starting from fermentation, the use of fermented gas for cooking and electricity, to the use of residual waste as organic fertilizer, as well as community service programs aimed at designing and implementing an organic fertilizer processing system and biogas filter based on the treatment of bio-slurry waste and baglog waste at the At-Tazkiyyah Qur'an House Sigh. The program is holistic between the community and university institutions of the University of Mataram.